The first Science Café in Laos - Cheah, P; Newton, P; Mayxay, M (Elsevier, 2016)
In Vientiane, Laos, on July 21, 2016, the University of Health Sciences, Ministry of Health, in collaboration with the Lao–Oxford–Mahosot Hospital–Wellcome Trust Research Unit, organised the first Science Café event in Laos. More than 50 students and staff of the Faculties of Medicine, Pharmacy, Dentistry, Nursing Sciences, Medical Technology, Basic Sciences, and Public Health attended the 2 h long event on Medical and Research Ethics. Lively discussions included what makes a research study ethical, what makes consent valid, and whether children should be involved as participants in clinical research.